Processing of BiFeO3 thin films to control their dielectric response - Reis, S. P. [UNESP]; Freitas, F. E. [UNESP]; Araujo, E. B. [UNESP] (Taylor & Francis Ltd, 2020)
BiFeO3 (BFO) thin films were studied to control their oxygen-related processing parameters in order to obtain specific electrical characteristics in terms of conductivity and dielectric relaxation. BFO thin films prepared with Fe and Bi excesses and post-annealed in oxygen atmosphere showed higher electrical conductivity and lower conduction activation energies than single phase ones. Distinct parameters indicated different conduction mechanisms in the films, associated with the first ionization of oxygen vacancies in BFO films with Fe and Bi excesses and the second one in single phase films. Higher conductive films show lower relaxation times compared to single phase ones.
Keywords: Conductivity; dielectric relaxation; bismuth ferrite; thin films